Lung-targeted delivery of TGF-beta antisense oligonucleotides to treat pulmonary fibrosis - Kim, Junghyun; Jeon, Seulgi; Kang, Seong Jae; Kim, Kyoung-Ran; Hien Bao Dieu Thai; Lee, Seokyung; Kim, Sehoon; Lee, Yun-Sil; Ahn, Dae-Ro (ELSEVIER, 2020)
Pulmonary fibrosis is a serious respiratory disease, with limited therapeutic options. Since TGF-beta is a critical factor in the fibrotic process, downregulation of this cytokine has been considered a potential approach for disease treatment. Herein, we designed a new lung-targeted delivery technology based on the complexation of polymeric antisense oligonucleotides (pASO) and dimeric human beta-defensin 23 (DhBD23). Antisense oligonucleotides targeting TGF-beta mRNA were polymerized by rolling circle amplification and complexed with DhBD23. After complexation with DhBD23, pASO showed improved serum stability and enhanced uptake by fibroblasts in vitro and lung-specific accumulation upon intravenous injection in vivo. The pASO/DhBD23 complex delivered into the lung downregulated target mRNA, and subsequently alleviated lung fibrosis in mice, as demonstrated by western blotting, quantitative reverse-transcriptase PCR (qRT-PCR), immunohistochemistry, and immunofluorescence imaging. Moreover, as the complex was prepared only with highly biocompatible materials such as DNA and human-derived peptides, no systemic toxicity was observed in major organs. Therefore, the pASO/DhBD23 complex is a promising gene therapy platform with lung-targeting ability to treat various pulmonary diseases, including pulmonary fibrosis, with low side effects.
Keywords: GROWTH-FACTOR-BETA; MOLECULAR-MECHANISMS; CYTOTOXICITY; BLEOMYCIN; PATHOGENESIS; PEPTIDES; DISEASE; INJURY; MICE